Integrated Approaches to Manage Multi-Case Families in the Criminal Justice System in Maricopa County, Arizona, and Deschutes and Jackson Counties, Oregon, 1999-2005 - Thoennes, Nancy ([Verlag nicht ermittelbar], 2009)
The project goal was to collect data on approximately 100 Unified Family Court (UFC) cases at each of the three selected jurisdictions -- Maricopa County, Arizona, Deschutes County, Oregon, and Jackson County, Oregon -- that have developed systems to address the special needs of families with multiple court cases. The purpose of the study was to examine research questions related to: (1) dependency case processing and outcomes, (2) delinquency case processing and outcomes, (3) domestic relations/probate case processing and outcomes, and (4) criminal case processing and outcomes. The data used in this study were generated from a review of the court records of 602 families including 406 families served by the UFC as well as comparison groups of 196 non-UFC multi-case families. During the study's planning phase, an instrument was drafted for use in extracting this information. Data collectors were recruited from former UFC staff and current and former non-UFC court staff. All data collectors were trained by the principal investigator in the use of the data collection form. The vast majority of all data extraction required a manual review of paper files. Variables in this dataset are organized into the following categories: background variables, items from dependency/abuse and neglect filings, delinquency filings, domestic relations/probate filings, civil domestic violence/protection order filings, criminal domestic violence filings, criminal child abuse filings, other criminal filings, and variables from a summary across cases.